Math, asked by lavish1906, 4 months ago

simplify (√3+√7)(√3-√7)​

Answers

Answered by prnkpani
3

Step-by-step explanation:

=(√3 + √7) (√3-√7)

= (√3)^2 - (√7)^2 (by using identity = (a-b)(a+b) = a^2 - b^2)

= 3 - 7

= - 5

Answered by ItzGarenafreefire2
2

Answer:

HEY MATE !!

HERE IS UR ANS ⤵️⤵️

(√3+√7) (√3-√7)

  • (√3+√3) (√7-√7)
  • here , we have to use (a+b)(a-b) = a²-b²
  • 3²-7²
  • 9-49
  • 40 (Ans)

... HOPE THIS HELPS U ALMOST ...

... THANK Q ...

Similar questions
Hindi, 4 months ago